Objective Structured Clinical Examinations practices across Canadian medical schools: A national overview - Gilchrist, Chris; Bismilla, Zia (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Introduction: Objective Structured Clinical Examinations (OSCEs) are crucial in assessing clinical competencies, but their implementation varies widely across medical schools. This work examines OSCE practices across Canadian medical schools, focusing on frequency, type, and timing.Methods: A survey was conducted among all 17 Canadian medical schools through the AFMC Clinical Skills Working Group. Data were collected during the 2023-2024 academic year. Details on OSCEs implementation during pre-clerkship and clerkship phases, categorized as formative or summative, and on the timing of final OSCEs was collected. Descriptive statistics were used to analyze the data.Results: The median number of OSCEs per school was four, with one-third formative and two-thirds summative. Pre-clerkship assessments were split between formative and summative OSCEs, while 78% of clerkship OSCEs were summative. Timing of a program’s final OSCE varied: 35% occurred before the last year, while 65% took place in the final year, predominantly in the second half. All final OSCEs were summative.Discussion and Conclusion: Variability in OSCE implementation likely reflects differing curricular approaches and institutional constraints. This work demonstrated a more balanced proportion of formative and summative assessments during pre-clerkship, indicating a desire to provide students with opportunities learn from feedback during their early training years. During clerkship, the focus shifted towards summative assessments. The later emphasis on summative OSCEs may highlight a focus on certifying competence at the cost of reduced opportunities for formative feedback. Medical schools may use these findings as guidance when building their programs of assessment.